On the heterogeneous nature of deformation in a strain-transformable beta metastable Ti-V-Cr-Al alloy. (1st January 2019) - Lilensten, L.; Danard, Y.; Brozek, C.; Mantri, S.; Castany, P.; Gloriant, T.; Vermaut, P.; Sun, F.; Banerjee, R.; Prima, F.
Abstract: Ti-10V-4Cr-1Al wt% (TVCA) is a new grade of titanium alloy, developed to combine twinning induced plasticity (TWIP) and transformation induced plasticity (TRIP) effects. The TVCA alloy exhibits a very high strain-hardening rate and an excellent balance between strength and ductility for great potential in aerospace applications. Deformation mechanisms are investigated using in-situ techniques as synchrotron X-ray diffraction (SXRD) and in-situ electron backscatter diffraction (EBSD) analysis during tensile strain, as well as transmission electron microscopy (TEM). The results reveal that permanent {332}<113> mechanical twinning and an unstable orthorhombic α" martensite are the major deformation products. This study aims at unveiling the interaction and co-deformation of the various deformation features, that lead to the outstanding mechanical properties of the alloy. The very high strain hardening rate could be explained by the simultaneous activation of two different deformation modes, the primary TRIP mode on one side, and the hybrid TWIP and secondary TRIP mode on the other one, in different grains, resulting in in-grain dynamic hardening (Hall-Petch)/softening (α" martensite) effects and meso-scale dynamic mechanical contrast. Selection of the deformation mechanism – TRIP or TWIP –, which seems to be inhomogeneous, at both the inter- and the intra-granular level, is investigated. Graphical abstract: Image 1